TEKNIK PEMATAHAN DORMANSI BENIH DAN PERTUMBUHAN JARAK PAGAR (Jatropha curcas L.) KULTIVAR IP-3P MELALUI PEMBERIAN GIBERELIN DAN BERBAGAI POSISI MIKROPIL DI PERSEMAIAN - Deby Juliana; Kovertina Rakhmi Indriana; Lia Amalia (Jurnal Agroekoteknologi, 2021)
This research aims to study and determine the technique of breaking the dormancy of Jatropha seeds by giving gibberellins (GA3) and various planting positions on the growth of Jatropha seeds in the nursery. The research was carried out from June-August 2020. The experimental design used was a simple randomized block design with a combination of GA3 concentrations and seed positions with 18 treatment combinations. Each was repeated two times. The results showed that giving gibberellin concentration at different planting positions did not have an effect on germination parameters, but it did affect growth parameters. All concentrations of GA3 had no effect on seed germination, seed growth rate and vigor index, but the concentration of 500 mg L-1 at various planting positions had a better effect on plant height, number of leaves, stem diameter, fresh weight and plant dry weight Jatropha in the nursery.